University Green Offices at the Intersection of Movement, Network, Market, and Hierarchy: A Case Study on the Production of Knowledge on ‘Sustainability’ as the Generation of Compromises at an Organizational Level - Elven, Julia (Springer Science and Business Media Deutschland GmbH, 2023)
This article empirically examines university Green Offices as a site of intersection of differing organizational conceptions of sustainability and, at the same time, as a context for the socialization of future leaders. It proceeds from reflection on the diversity of orders of knowledge around sustainability within the academic field, which are also associated with differing priorities of action, coordination, and justification. The concept of ‘economics of convention’ (économie des conventions; EC), as developed by French economists and sociologists, provides us with an analytical framework that, taking regimes of coordination and justification into consideration, can structure this diversity. Based on an ongoing qualitative case study, the paper details the various logics of coordination and narratives of justification encountered in the work of the university Green Office. The findings of the case study indicate that these logics have differing advantages and drawbacks, meaning that work toward a mutually beneficial compromise is preferable to the suppression of particular logics. I proceed from the fundamental assumption that the ability to identify and understand these logics, which on occasion conflict substantively, offers a major advantage for future leadership and decision-making.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Compromise devices; Economics of convention; Higher education; Organization studies; Sustainable practices